2018
DOI: 10.5173/ceju.2018.1618
|View full text |Cite
|
Sign up to set email alerts
|

Potential clinical applications of microRNAs as biomarkers of renal cell carcinoma

Abstract: IntroductionRenal cell carcinoma (RCC) accounts for 3% of adult malignancies and more than 90% of kidney neoplasms. High rates of undiagnostic percutaneous kidney biopsies and difficulties in reliable pre-operative differentiation between malignant and benign renal tumors using contemporary imaging techniques result in large numbers of redundant surgeries. Absence of specific biomarkers for early detection and monitoring complicates on-time diagnosis of the disease and relapse. For the patients followed up aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The potential significance of miRNAs as diagnostic and prognostic biomarkers in renal cell carcinoma has been confirmed by multiple studies [274][275][276]. These small molecules participate in the regulation of RCC cell growth, cell cycle, apoptosis, angiogenesis, tissue invasion, and metastasis [277]. Noteworthy, miRNAs may be useful markers, allowing for the selection of patients to treatment.…”
Section: Renal Cancermentioning
confidence: 92%
“…The potential significance of miRNAs as diagnostic and prognostic biomarkers in renal cell carcinoma has been confirmed by multiple studies [274][275][276]. These small molecules participate in the regulation of RCC cell growth, cell cycle, apoptosis, angiogenesis, tissue invasion, and metastasis [277]. Noteworthy, miRNAs may be useful markers, allowing for the selection of patients to treatment.…”
Section: Renal Cancermentioning
confidence: 92%
“…As shown in the above tables, several metastamiRs have been postulated to be useful as potential biomarkers of prognosis, disease progression, or metastasis. Several metastamiRs could also serve as potential predictors for responsiveness to chemotherapeutic regimens (229). One of the more promising prognosticators for disease progression is the oncomiR miR-21, as several studies have commented on its potential utility as a ccRCC-specific miRNA signature of disease progression (24,25,135,193).…”
Section: Mirnas As Biomarkers or Therapy In Rccmentioning
confidence: 99%
“…For example, miR-21, miR-29 and miR-192, as key regulators, play an important regulatory role in the progression of renal brosis [8][9][10]. Related studies have shown that many miRNAs (such as miR-15a and miR-210) may become new tools for the detection, treatment and prognosis of renal cancer [11][12][13]. Moreover, miR-34a-5p, miR-27a and miR-126 have also been shown to be involved in the development of diabetic nephropathy [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%